Assessment of cardiovascular risk factors in coronary heart disease - Eszter Szabados; Kálmán Tóth; Anita Pálfi (Cardiologia Hungarica)
The SUrvey of Risk Factors in Coronary Heart Disease (SURF-CHD) II study was conducted in 29 countries, including Hungary, to assess the efficacy of secondary prevention of coronary heart disease. The cross-sectional survey was conducted from 2019 to 2022 among patients with coronary heart disease attending routine outpatient visits, reporting recorded risk factors, achievement of target values of main risk factors, medical treatment, participation in cardiac rehabilitation programs, and the effect of educational level on risk factor control. The SURF CHD II study concluded that achievement of risk factor targets is low among CHD patients worldwide. The target attainment was the lowest for waist circumference which was achieved by 12.1% of the Hungarian patients and 15.9% of all examined patients. The LDL-cholesterol target value <1.4 mmol/L was achieved by 17.2% of Hungarian patients, 20.8% of all examined patients, the LDL-cholesterol target value <1.8 mmol/L was achieved by 40.8% of the overall population and 41.4% of the Hungarian patients. 82.4% of Hungarian patients and 78.7% of all examined patients were non-smokers (or ex-smokers). Participation in cardiac rehabilitation is low worldwide and below expectations, patients with higher educational level were more likely to participate in cardiac rehabilitation, use cardioprotective medication, and meet risk factor targets.